Exploring Saidian Orientalism in Amitav Ghosh's Sea of Poppies from a postcolonial perspective - HADJIRA, Asma; SELT, Djihad Affaf (Faculty of Letters and Foreign Languages Department of English, 2019)
The rich cultural legacy of colonialism still needs more study. Throughout recent years, postcolonial studies have been emerging and developing to shed light on different issues related to the postcolonial world. This latter has its own atmosphere, that is characterized by pain, sorrow and memories. Thus, the postcolonial literature is known for its special tone of intellectual resistance. Works in this field needed their own theories so that they can be examined academically through the postcolonial theory that has emerged to give this genre of literature credibility and reliability. In addition, the out-break of Saidian Orientalism has contributed remarkably in promoting the value of postcolonial literature as it investigates the relations between the two poles of the world the West and the East. This project explores the use of Saidian Orientalism along with the postcolonial theory in Sea of Poppies (2008) written by the Indian writer Amitav Ghosh. It also investigates the common elements and the important notions of the two theories. By studying this topic, it is aspired that this dissertation will contribute to studies done under the shade of postcolonial studies